Program Penalaran Islam Indonesia dan Gerakan Kontra-Radikalisme - Mas'ud, Ali; Jazil, Saiful; Subty, Taufik; Fahmi, Muhammad (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2019)
This article dscribes the importance of Indonesian Islam Reasoning Program (PPII) as the supplement of Islamic Education (PAI) materials bringing peace for the universe and counter radicalism movement in UIN Sunan Ampel Surabaya. Data was collected through observation, intervoews, and documentation. Findings shows that PPII established Islamic foundation based upon contextual Islamic theology, Sufism expression, contextual Islamic law, and genealogy of Islamic civilization in Indonesia. Therefore, peace Islamic attitudes, highest endeavor, and Islamic reasoning can be internalized into disciplines that students take. Observing more visible radical Islamic movement in public sphere, PPII takes important position in countering radicalism. Materials in PPII are synergic to Islamic Education materials with rational-empirical reasoning, which is epistemologically aligned with Burhani approach.